2013
DOI: 10.1039/c2sm27000e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using binary mixtures of zwitterionic and charged lipids on nanodisc formation and stability

Abstract: Nanodiscs are self-assembled $10 nm particles composed of lipid bilayer patches, stabilized by helical amphipathic belt proteins. The size, monodispersity and well-defined structure make the nanodiscs a popular model for the biological cell membrane, especially for structural and functional studies of membrane proteins. The structures and properties of nanodiscs made of zwitterionic lipids are well known. However, the biological cell membrane is negatively charged and thus nanodiscs containing anionic lipids s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…The stability of Nanodiscs with respect to thermal unfolding and prolonged storage was compared for discs with binary mixtures of zwitterionic DMPC, negatively charged DMPA or DMPG, and with the synthetic cationic lipid DMTAP. 189 A high yield of Nanodiscs could be obtained for all mixtures of DMPC and DMPG, but DMPA at higher than 25% fraction and DMTAP at more than 10%, destabilized Nanodiscs and precipitated at high concentrations. On the other hand, 25% DMPG stabilized Nanodiscs with respect to prolonged storage and to thermal denaturation probed as by DSC.…”
Section: Structure and Assembly Of Nanodiscsmentioning
confidence: 94%
“…The stability of Nanodiscs with respect to thermal unfolding and prolonged storage was compared for discs with binary mixtures of zwitterionic DMPC, negatively charged DMPA or DMPG, and with the synthetic cationic lipid DMTAP. 189 A high yield of Nanodiscs could be obtained for all mixtures of DMPC and DMPG, but DMPA at higher than 25% fraction and DMTAP at more than 10%, destabilized Nanodiscs and precipitated at high concentrations. On the other hand, 25% DMPG stabilized Nanodiscs with respect to prolonged storage and to thermal denaturation probed as by DSC.…”
Section: Structure and Assembly Of Nanodiscsmentioning
confidence: 94%
“…This includes commonly used neutral detergents, as well as zwitterionic membrane lipids used in lipid nanodiscs or nanoparticles. With the ambition to mimic cellular membranes, it is reasonable to include negatively charged head groups in the membrane mimetic [ 88 , 89 ]. Ψ I comprises the electric potentials of the hydrocarbon core of the lipid membrane.…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%
“…Thermal stability of nanodiscs is important for various applications including the biophysical and structural studies of membrane proteins [34,35] . Experimental studies have reported that peptide or MSP based nanodiscs can be stable up to ~ 60 C. [36] Thermal unfolding has been seen with further increase in temperature that destabilizes the nanodisc's size.…”
Section: Thermal Stability Of Polymer-nanodiscsmentioning
confidence: 99%